ACL word segmentation correction - Nastase, Vivi; Hitschler, Julian (Universität, 2019)
The data in this collection consists of two parallel directories, one ("raw") containing the raw text of 18850 articles from the ACL 2013/02 collec...
Production date 2018
Gesehen am 16.07.2019
Keywords: Forschungsdaten; Datenbank